2017
DOI: 10.1007/s00199-017-1089-1
|View full text |Cite
|
Sign up to set email alerts
|

Assigning pollution permits: are uniform auctions efficient?

Abstract: We study the efficiency of the uniform auction as an allocation mechanism for emission permits among polluting firms. In our model, firms have private information about their abatement costs, which differ across firms and across units, and bidders' demands are linear. We show that there is a continuum of interior Bayesian-Nash equilibria, and only one is efficient, minimizing abatement costs. We find that the existence of many bidders is not a sufficient condition to guarantee an efficient equilibrium in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Khezr and MacKenzie [31] also showed that a uniform auction with allowance reserve could lead to distortion by unintentionally raising the clearing price higher. Alvarez et al [32] performed a theoretical assessment on the efficiency of uniform auctions as a means of allocating allowances. He showed that for a uniform auction to be effective there should be no correlation between the types of bidders as well as many bidders.…”
Section: Literature Review Of Consignment Auctionmentioning
confidence: 99%
“…Khezr and MacKenzie [31] also showed that a uniform auction with allowance reserve could lead to distortion by unintentionally raising the clearing price higher. Alvarez et al [32] performed a theoretical assessment on the efficiency of uniform auctions as a means of allocating allowances. He showed that for a uniform auction to be effective there should be no correlation between the types of bidders as well as many bidders.…”
Section: Literature Review Of Consignment Auctionmentioning
confidence: 99%
“…This approach is consistent with simple and direct assignment mechanisms such as grandfathering and benchmarking. Since auctioning is becoming more relevant as a way to distribute the permits (for recent developments see [20][21][22]), a relevant (although technically complex) extension would be to endogenize the initial allocation by considering auctioning mechanisms.…”
Section: Concluding Remarks Policy Implications and Future Researchmentioning
confidence: 99%